Longhorns east - Boggs, Johnny D. (Kensington Publishing Corp., 2023)
"Tom Candy Ponting was no ordinary trail boss. He didn't smoke, chew, cuss, or even carry a gun. Unlike his competitors, he learned how to herd cows on a farm back in England -- and how to handle cowboys in bareknuckle prizefights. But his skills and know-how were really put to the test when he accepts a bet he might live to regret: lead a cattle drive from Texas to New York City. Not one to back down on a dare, Ponting assembles the motliest crew of cowboys ever seen -- Texans, Englishmen, Mexicans, Freemen, Cherokee -- and charts a course through the unfriendliest country to move seven hundred head of cattle, never easy in the best of times. Along the way, they'll cross railroads and rustlers, hucksters and hustlers, with detours and dead ends aplenty. But if they succeed, the team will make more than just a whole lot of money. They will make history. . . . Inspired by the real-life adventures of legendary cattleman Tom Candy Ponting, Longhorns East takes readers on an unforgettable journey as big and bold as the American Dream itself." -- from Amazon.com